An Investigation into Understanding Postcolonial Theory Using Textual ReaderResponse Strategies. The Case of Master One Students of English and Teachers at Ammar Thelidji University - Zenati, Ibrahim Khaled; NOUIOUA,Wafa (University of Ammar Theledji -Laghouat, 2020)
The present dissertation aimed to investigate the role of teaching the modern African novel in enhancing master one LMD students’ understanding of postcolonial theory. Besides, this work shed light on the textual reader-response strategies (TRRS) and verified their effectiveness in teaching modern African literature in the department of English at Ammar Thelidji University of Laghouat. It was a descriptive study, which was based on a descriptive method, in which a questionnaire was directed to 20 students and 05 teachers was used. In this respect, both quantitative and qualitative approaches were used to evaluate the efficacy of (TRRS) in promoting the understanding of postcolonial theory. This research was divided into three chapters: the first chapter clarified the relationship between postcolonial theory and modern African literature. It provided the reader with a definition of postcolonial theory and modern African literature, and then it elaborated the connection between them. The second chapter dealt with reader-response theory and its strategies. The third chapter involved the analysis and the interpretations of the study’s questionnaire for both teachers and students. Therefore, the research findings indicated that the use of (TRRS) in teaching modern African novel is an effective method in fostering the students’ understanding of postcolonial theory. Hence, it is required to be used to teach postcolonial theory in African literature class